DAMPAK COMPANY SIZE, KINERJA KEUANGAN, KOMISARIS INDEPENDEN, DAN FAKTOR LAINNYA PADA EARNINGS MANAGEMENT - VIORENCIA HENDRANATA; Apit Susanti (E-Jurnal Akuntansi TSM, 2021)
The goal of this research is to gather empirical evidence about the impact of company size, financial performance, independent commissioners, institution ownership, financial leverage, board size, free cash flow, and managerial ownership as independent variables on earnings management as a dependent variable. Population of this research are companies that listed in Indonesia Stock Exchange, especially in non-financial sector during 2017-2020. The sample selection process was carried out by using the purposive sampling method and based on predetermined sample selection criteria so it generated 70 companies that met the criteria with a total of 280 data used. Multiple regression method was used to analyze the data. The result of this research exposed that financial performance and free cash flow have impact on earnings management, this is because companies with lots of free cash flow indicate there is enough capital to meet financial needs so that management may no longer be compelled to manipulate earnings to attract investors' attention, while the increase in profitability, the practice of profit manipulation is also increasing. However, company size, independent commissioners, institution ownership, financial leverage, board size, and managerial ownership have no impact on earnings management.